2005
DOI: 10.5507/bp.2005.064
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antioxidant Effect of Stobadine Derivative in Condition of Kidney Ischemia-Reperfusion in a Pre-Clinical Experiment (Effect in Prophylaxis)

Abstract: The goal of the study was to monitor the antioxidative effect of stobadine derivative in the conditions of ischemia-reperfusion of laboratory rat kidney tissue. The animals were divided by random selection into 5 groups (n = 10). The treated groups were given stobadine derivate in peroral doses of 5, 10 and 20 mg/kg in 0.5 % solution of Avicel once a day; the placebo group was given only the solution of Avicel. The last group was an intact group (without ischemia-reperfusion and without treatment). After concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Ischaemia–reperfusion injury is one of the main causes of acute renal failure and the clinical diagnosis is usually made after the injury has already occurred. Previous studies have demonstrated a promising effect of oral heptanoylstobadine administration against renal I/R injury 14,15 . In these previous studies, heptanoylstobadine was administered 15 days before I/R (to examine its prophylactic effect) or after 60 min ischaemia and 10 min reperfusion (to examine its therapeutic effect).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ischaemia–reperfusion injury is one of the main causes of acute renal failure and the clinical diagnosis is usually made after the injury has already occurred. Previous studies have demonstrated a promising effect of oral heptanoylstobadine administration against renal I/R injury 14,15 . In these previous studies, heptanoylstobadine was administered 15 days before I/R (to examine its prophylactic effect) or after 60 min ischaemia and 10 min reperfusion (to examine its therapeutic effect).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a promising effect of oral heptanoylstobadine administration against renal I/R injury. 14,15 In these previous studies, heptanoylstobadine was administered 15 days before I/R (to examine its prophylactic effect) or after 60 min ischaemia and 10 min reperfusion (to examine its therapeutic effect). Although the anti-oxidant effects of stobadine in the kidney were demonstrated in these previous studies, no beneficial effects were noted in terms of serum urea and creatinine, which are common physiologial markers of kidney function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it significantly attenuated lipid peroxidation [ 18 ]. Stobadine, a pyridoindole derivative that displays cardioprotective and antiarhythmical effects, showed a protective effect during I/R by increasing the glutathione peroxidase activity and the total antioxidant capacity [ 36 ]. ACE inhibitors and calcium antagonists, especially the dihydropyridines, possess radical scavenging properties and prevent ROS formation.…”
Section: Discussionmentioning
confidence: 99%